The Influence of Profitability and Stock Value on Company Value With Dividend Policy as an Intervening Variable (Empirical Study of Garment Companies Listed on the Idx for the 2018-2022 Period) - Angelina Capah; Cahyo Promono (Yayasan Multidimensi Kreatif, 2024)
This research was conducted on garment companies listed on the IDX for the 2018-2022 period with the aim of analyzing the influence of profitability and share value on company value which is mediated by dividend policy. The research population was 5 garment companies and the number of observations made was 25 observations over five periods from 2018-2022. The data sources used are secondary data and data collection techniques use documentation. The data analysis technique uses the classic assumption test, hypothesis test and Sobel test. The results of the research conducted show that profitability and the value of company shares do not partially have a significant effect on dividend policy in garment companies listed on the BEI, profitability and the value of company shares partially have a significant effect on the value of garment companies listed on the BEI, dividend policy has a significant effect on company value the garment is listed on the IDX. Dividend policy does not mediate the influence between profitability and share value and the value of garment companies listed on the IDX.